2013
DOI: 10.1097/sla.0b013e31828fe1b2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes for Open and Laparoscopic Midline Incisional Hernia Repair

Abstract: : Postoperative pain or recovery at 3 weeks after repair of midline incisional hernias does not differ between LR and OR, but the LR results in better physical function and less surgical site infections than the OR does. (ClinicalTrials.gov Identifier: NCT00472537).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 26 publications
4
66
0
Order By: Relevance
“…The laparoscopic approach for incisional and primary ventral hernia has gained popularity because of its low recurrence, short hospital stay and low complication rates compared with the open repair approach [2,4,5,30]. However, it was observed that as many as onefourth of patients have poor outcome following laparoscopic ventral hernia repair [1].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The laparoscopic approach for incisional and primary ventral hernia has gained popularity because of its low recurrence, short hospital stay and low complication rates compared with the open repair approach [2,4,5,30]. However, it was observed that as many as onefourth of patients have poor outcome following laparoscopic ventral hernia repair [1].…”
Section: Discussionmentioning
confidence: 98%
“…Many recently published articles consistently report good laparoscopic ventral and incisional hernia repair (LVIHR) outcomes [1][2][3][4]. LVIHR continues to demonstrate low rates of wound complications and short hospital stays [5].…”
Section: Introductionmentioning
confidence: 98%
“…Another limitation is the lack of a standard quality of life assessment such as SF-36 or Carolinas Comfort Scale (CCS). 14,15 This, however, would only be of value if measured in all patients with or without an incisional hernia. In addition, any comparison between such groups would suffer from other differences that emerge from nonrandomized groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Five RCTs were carried out in both the Netherlands [29][30][31][32][33] and Spain [34][35][36][37][38]. [44][45][46] 3 Pakistan [40], [47] Turkey [39], [48] Italy [49,50]Germany [28], [51] 2 Sweden [52] USA [53] Australia (54) Lithuania [55] France [56] Belgium [57] Denmark [58] 1 -Multi vs Single-centre…”
Section: Study Demographicsmentioning
confidence: 99%
“…Multi centre [28][29][30], [32][33][34], [40], [49], [51][52][53], [57][58] 13 Single centre [31], [35][36][37][38][39], [41][42][43][44][45][46], [48][49][50], [54][55][56] 18 -Year of Publication 1995-2005 [28], [30], [32], [35][36], [39], [46] 7 2006-2016 [29], [31], [33][34], [37][38], [40][41][42][43][44][45], [47]…”
Section: Study Demographicsmentioning
confidence: 99%